Ответ:
[tex] \frac{7}{15} - ( \frac{2}{15} + \frac{1}{5} ) = \frac{7}{5} - \frac{1}{3} = \frac{16}{15} = 1 \times \frac{1}{15} [/tex]
[tex] \frac{3}{16} + ( \frac{15}{16} - \frac{5}{8} ) = \frac{3}{16} + \frac{5}{16} = \frac{1}{2} = 0.5[/tex]
Пошаговое объяснение:
Сделай ответ лучшим, пж
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
б) 3/16 + (15/16 - 10/16) = 3/16 + 15/16 - 10/16 = 8/16 = 1/2
Verified answer
Ответ:
[tex] \frac{7}{15} - ( \frac{2}{15} + \frac{1}{5} ) = \frac{7}{5} - \frac{1}{3} = \frac{16}{15} = 1 \times \frac{1}{15} [/tex]
[tex] \frac{3}{16} + ( \frac{15}{16} - \frac{5}{8} ) = \frac{3}{16} + \frac{5}{16} = \frac{1}{2} = 0.5[/tex]
Пошаговое объяснение:
Сделай ответ лучшим, пж